The Relationship Between Talent Management And Work Engagement: Role Of Psychological Capital As Mediator - Bibi, Dr. Palwasha; Rahman, Dr. Haji; Shah, Dr. Muhammad Anees ul Husnain; Ali, Dr. Nazim; Akbar, Dr. Neelam; Ahmad, Dr Ashfaq (Migration Letters, 2024)
This study aims to examine the relationship between talent management (TM) and work engagement (WE) among faculty members working in universities in the public sector in Khyber Pakhtunkhwa, Pakistan. This study is also to examine how psychological capital (PC) acts as a mediator in the relationship between TM and WE. The study utilised a quantitative technique, namely path analysis, to investigate the relationship between several parameters. The sample encompassed teachers from public sector teaching institutions, comprising a collective of 443 respondents. The study included closed questionnaires that were evaluated using a Likert scale with five possibilities, spanning from 1 (strongly disagree) to 5 (strongly agree). The data were comprehensively collected over a period of approximately two months. The findings confirmed that TM had a positive influence on both WE and PC. Moreover, this study suggests that PC plays a role as a mediator in the relationship between TM and WE.